Directories of mathematics web sites: principles of composition - Burgis, Bronislovas (Lietuvos matematikos rinkinys, 2021)
Who and how should prepare the list of web sites for the specific math course? In the article we discuss the principles of selection taking into consideration topics, methods of teaching, and relations between the web sites. Our proposal is to prepare your own list (directory) for every course.
Keywords: math web sites; directories; methods of selection